Constructing A Scale For The Achievement Motivation In Learning Science At The Primary Stage Based On Atkinson Theory - Manal Mohammed Khaleel Abu-Za’rour; Monim Abdulkareem Al-Sa’aideh (European Scientific Journal, ESJ, 2016)
The aim of this study is to construct a scale to measure the achievement motivation in learning science at the primary stage. The study population consists of the students of the third primary class. The study subjects were 193 students. The scale validity was confirmed through four methods: arbitrators’ validity, content validity, factor validity, and the correlation validity of the scale items with the total degree and domain degree. The scale reliability was ensured through two methods: test-retest and the internal consistency. Results showed acceptable significant validity and reliability of the scale. The coefficient values of the item saturation with their domains (factor validity) were 0.347-0.802. Co-efficient co-relations of items with the total degree were 0.332-0.550. Also, the correlations of items with their domains were 0.438-0.694. As for the scale reliability, the internal consistency value (Cronbach’s Alpha) was 0.703 and 0.802 by using the stability coefficient.